Macrophage membrane-coated iron oxide nanoparticles for enhanced photothermal tumor therapy. (13th February 2018) - Meng, Qian-Fang; Rao, Lang; Zan, Minghui; Chen, Ming; Yu, Guang-Tao; Wei, Xiaoyun; Wu, Zhuhao; Sun, Yue; Guo, Shi-Shang; Zhao, Xing-Zhong; Wang, Fu-Bing; Liu, Wei
Abstract: Nanotechnology possesses the potential to revolutionize the diagnosis and treatment of tumors. The ideal nanoparticles used for in vivo cancer therapy should have long blood circulation times and active cancer targeting. Additionally, they should be harmless and invisible to the immune system. Here, we developed a biomimetic nanoplatform with the above properties for cancer therapy. Macrophage membranes were reconstructed into vesicles and then coated onto magnetic iron oxide nanoparticles (Fe3 O4 NPs). Inherited from the Fe3 O4 core and the macrophage membrane shell, the resulting Fe3 O4 @MM NPs exhibited good biocompatibility, immune evasion, cancer targeting and light-to-heat conversion capabilities. Due to the favorable in vitro and in vivo properties, biomimetic Fe3 O4 @MM NPs were further used for highly effective photothermal therapy of breast cancer in nude mice. Surface modification of synthetic nanomaterials with biomimetic cell membranes exemplifies a novel strategy for designing an ideal nanoplatform for translational medicine.